Mandibular Fracture Patterns at a Medical Center in Central Taiwan: A 3-Year Epidemiological Review. Issue 51 (December 2017) - Lin, Fu-Yu; Wu, Chao-I; Cheng, Hsu-Tang
Abstract : Abstract: Mandibular fractures constitute a major portion of maxillofacial trauma and may lead to considerable functional and aesthetic sequelae if treatment is inadequate or delayed. An epidemiology study on mandibular fractures may guide the preventive efforts of the Taiwan public health care system. Therefore, a retrospective review was conducted at a medical center in central Taiwan to evaluate the current mandibular fracture epidemiology. The medical records and digitized radiographs of 198 patients who received treatment for mandibular fractures during a 3-year period (from October 2010 to September 2013) at a medical center in central Taiwan were reviewed to obtain demographic and injury data. The average age was 29.4 years (3–82 years). Patients aged 21 to 30 years sustained the most mandibular fractures (62 patients, 31.3%). The overall sex distribution (male to female) ratio was 1.8. Motor-vehicle accidents (MVAs) were the most common mechanism of injury (162 patients, 82%), and scooter and motorcycle riders wearing partial-coverage helmets constituted the majority of patients. A chart review identified 198 patients with 335 mandibular fractures; 113 patients (57.1%) had multiple mandibular fractures. The most common fracture sites were the symphysis and parasymphysis regions (38.9%), followed by the condyle (26.0%), angle (14.3%), body (14.3%), and ramus (6.6%). MVAs are the major cause of mandibular fractures in central Taiwan, and patients aged <30 years sustained the most mandibular fractures. Compared with previous studies, the present study has a higher percentage of women with mandibular fractures. In addition, inadequate mandibular protection by partial-coverage helmets may be a major reason for mandibular fractures most commonly localized in the symphysis and parasymphysis regions. The incidence and causes of mandibular fractures may reflect the trauma patterns within the community, thus facilitating the development of a preventive strategy for the socioeconomic and environmental background of central Taiwan.